The role of clinical supervision in implementing evidence-based practice for managing comorbidity. Issue 1 (2nd January 2021) - Giannopoulos, Vicki; Morley, Kirsten C.; Uribe, Gabriela M.; Louie, Eva; Wood, Katie; Teesson, Maree; Baillie, Andrew; Haber, Paul S.
ABSTRACT: Although effective evidence-based treatments exist for comorbid mental health and substance use disorders, they are not widely implemented. This paper reports a case study of the clinical supervision component of a multimodal training program provided to 20 counselors working in addictions which aimed to increase implementation of evidence-based practise when managing comorbidity. Implementation barriers and facilitators observed during the supervision process will be discussed. The clinical supervision was provided by telephone with significant improvements in counselor self-efficacy and fidelity observed following supervision. These findings suggest that clinical supervision can assist in facilitating implementing of evidence-based interventions.